Speeding financial inclusion - Kochhar , Sameer (New York, 2009)
Scaling-up access to finance for India's rural poor presents a formidable developmental challenge in a country as vast and varied as India. It was in this context that Skoch Development Foundation undertook the first-ever nationwide multi-stakeholder study entitled "National Study on Speeding Financial Inclusion". This study sought to collate primary research based on our grassroots experiences from several project sites and field visits; and, views from all stakeholders so as to arrive at key interventions and intermediations to speed up the process of financial inclusion, and thereby poverty alleviation. Apart from providing key recommendations in the form of a roadmap to speed up the process of financial inclusion, the study also sought to determine the viability and cost-effectiveness of the Business Correspondent (BC) model and has identified several options to make the model viable.
Keywords: Finance - Social aspects - India